Ovulatory signals alter granulosa cell behavior through YAP1 signaling - Tianyanxin Sun; Francisco J. Diaz (BMC, 2019)
Abstract Background The Hippo pathway plays critical roles in regulating cell proliferation, differentiation and survival among species. Hippo pathway proteins are expressed in the ovary and are involved in ovarian function. Deletion of Lats1 causes germ cell loss, ovarian stromal tumors and reduced fertility. Ovarian fragmentation induces nuclear YAP1 accumulation and increased follicular development. At ovulation, follicular cells stop proliferating and terminally differentiate, but the mechanisms controlling this transition are not completely known. Here we explore the role of Hippo signaling in mouse granulosa cells before and during ovulation. Methods To assess the effect of oocytes on Hippo transcripts in cumulus cells, cumulus granulosa cells were cultured with oocytes and cumulus oocyte complexes (COCs) were cultured with a pSMAD2/3 inhibitor. Secondly, to evaluate the criticality of YAP1 on granulosa cell proliferation, mural granulosa cells were cultured with oocytes, YAP1-TEAD inhibitor verteporfin or both, followed by cell viability assay. Next, COCs were cultured with verteporfin to reveal its role during cumulus expansion. Media progesterone levels were measured using ELISA assay and Hippo transcripts and expansion signatures from COCs were assessed. Lastly, the effects of ovulatory signals (EGF in vitro and hCG in vivo) on Hippo protein levels and phosphorylation were examined. Throughout, transcripts were quantified by qRT-PCR and proteins were quantified by immunoblotting. Data were analyzed by student's t-test or one-way ANOVA followed by Tukey's post-hoc test or Dunnett's post-hoc test. Results Our data show that before ovulation oocytes inhibit expression of Hippo transcripts and promote granulosa cell survival likely through YAP1. Moreover, the YAP1 inhibitor verteporfin, triggers premature differentiation as indicated by upregulation of expansion transcripts and increased progesterone production from COCs in vitro. In vivo, ovulatory signals cause an increase in abundance of Hippo transcripts and stimulate Hippo pathway activity as indicated by increased phosphorylation of the Hippo targets YAP1 and WWTR1 in the ovary. In vitro, EGF causes a transient increase in YAP1 phosphorylation followed by decreased YAP1 protein with only modest effects on WWTR1 in COCs. Conclusions Our results support a YAP1-mediated mechanism that controls cell survival and differentiation of granulosa cells during ovulation.